Evaluation in Accuracy to Two Impression Techniques: In Case of Bone Anchored Bridge - Sularsih Sularsih; O. Ishida; Meinar Nur Ashrin; M. Okajima; T. Ichikawa (Faculty of Dentistry, Universitas Indonesia, 2013)
Purpose: The purpose of this study was to investigate and compare the accuracy of two procedures: open tray with splinting technique and closed tray impression techniques, in innovative in vitro experiments. Materials and Methods: One master cast was fabricated with 4 abutment replica implants with almost parallel position in an anterior region of an edentuloys mandibular plaster cast. The working cast was taken impessions with open tray splinting technique (group 1) and closed tray technique (group 2) using polyvinyl siloxane impression material. The Type III dental stone ws poured into around the impressions. The accuracy of impression procedured were measured 24 hours long after pouring dental stone to each impression. Four sited were marked to measured on every platform of implant analogs. The analyzing stylus was positioned to each site and the heights, horizontal inclination and saggital incliniation were measured using the Laser displacement transducer (LK G115; Keyence, Osaka, Japan). Measurements of these 16 points of four implants per a model was repeated 7 times under the same condition. The gap between the abutment and superstructure at one screw test was evaluated with a digital microscope system (VH-Z100 & VH-5000; Keyence, Osaka, Japan). The mean and standard deviation estimated from the samples of each subgroup were statistically analyzed by ANOVA test (P<0.05 as the level of significance). Results: The relative differences of implant heights, horizontal inclination and saggital inclination of each implant on closed tray technique was statistically different to master cast and open tray with splinting (P<0.005). Conclusion: The open tray technique was more accurate comparing to the closed tray technique. The gap between the abutment and superstructure in the open tray with splinting technique was smaller comparing to closed tray technique. DOI: 10.14693/jdi.v17i1.111